Major expansion of marine forests in a warmer Arctic - Assis, Jorge (2022)
Accelerating warming and associated loss of sea ice are expected to promote the expansion of coastal marine forests (macrophytes) along the massive Arctic coastlines. Yet, this region has received much less attention compared to other global oceans. The available future projections of Arctic macrophytes are still limited to few species and regions, and mostly focused at lower latitude ranges, thus precluding well-informed IPCC impact assessments, conservation and management. Here we aim to quantify potential distributional changes of Arctic intertidal and subtidal brown macroalgae and eelgrass by the year 2100, relative to present. We estimate habitat suitability by means of species distribution modeling, considering changes in seawater temperature, salinity, nutrients and sea ice cover under two greenhouse gas emission scenarios, one consistent with the Paris Agreement (RCP 2.6) and the other representing limited mitigation strategies (RCP 8.5). As data on substrate conditions do not exist, the models were restricted to the depth range supporting Arctic macrophytes (down to 5 m for eelgrass and 30 m for brown macroalgae). Models projected major expansions of Arctic macrophytes between 69,940 and 123,360 km2, depending on the climate scenario, with polar distribution limits shifting northwards by up to 1.5 latitude degrees at 21.81 km per decade. Such expansions in response to changing climate will likely elicit major changes in biodiversity and ecosystem functions in the future Arctic. Expansions are, however, less intense than those already realized over the past century, indicating an overall slowing down despite accelerated warming as habitats become increasingly occupied..